Corporate Social Responsibility Sebagai Promosi Perseroan Terbatas - Yusuf, Chandra; Purwaningsih, Endang (UI Scholars Hub, 2019)
The application of Corporate Social Responsibility (CSR) and Fiduciary Duty in Law No. 40 of 2007 concerning Limited Liability Companies creates a conflict of interest. The problem that arises is the placement of CSR in the company's income statement that will reduce the company's dividend distribution. This violates the principle of